2003
DOI: 10.1021/es026301l
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrate Composite for Ocean Carbon Sequestration

Abstract: Rapid CO2 hydrate formation was investigated with the objective of producing a negatively buoyant CO2-seawater mixture under high-pressure and low-temperature conditions, simulating direct CO2 injection at intermediate ocean depths of 1.0-1.3 km. A coflow reactor was developed to maximize CO2 hydrate production by injecting water droplets (e.g., approximately 267 microm average diameter) from a capillary tube into liquid CO2. The droplets were injected in the mixing zone of the reactor where CO2 hydrate formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 35 publications
(70 reference statements)
2
111
0
1
Order By: Relevance
“…During the past 15 years the emphasis has been on natural gas storage and transportation (Gudmundsson et al, 2000;Matsuda et al, 2006;Thomas and Dawe, 2003) and on carbon dioxide capture from flue and fuel gases (Aaron and Tsouris, 2005;Kang and Lee, 2000;Klara and Srivastava, 2002;Linga et al, 2007a;Seo et al, 2005). Hydrate formation is also a factor when considering injection of CO 2 into the ocean (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007. If hydrate is to be formed from liquid water then the efficient contacting of the gas with water plays a key role in the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 15 years the emphasis has been on natural gas storage and transportation (Gudmundsson et al, 2000;Matsuda et al, 2006;Thomas and Dawe, 2003) and on carbon dioxide capture from flue and fuel gases (Aaron and Tsouris, 2005;Kang and Lee, 2000;Klara and Srivastava, 2002;Linga et al, 2007a;Seo et al, 2005). Hydrate formation is also a factor when considering injection of CO 2 into the ocean (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007. If hydrate is to be formed from liquid water then the efficient contacting of the gas with water plays a key role in the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, other arrangements such as bubbles dispersed in water or water droplets injected into a gas atmosphere have been proposed (Gudmundsson et al, 2000;McCallum et al, 2007;Ohmura et al, 2002;Tsuji et al, 2004). Tsouris and co-workers have presented novel and efficient crystallizers in the context of CO 2 sequestration work (Lee et al, 2003;Tsouris et al, 2004Tsouris et al, , 2007West et al, 2001). In addition, it has also been reported that when hydrate is formed from ice, temperature ramping enhances the conversion (Susilo et al, 2007b;Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrate technology has advanced to greater proportions: implementing the high latent heats as refrigerant [1], safe carbon capture as carbon sequestration [2] in hydrates, purifying rare gases [3] in hydrates, and safe efficient transport of energy [4] using rapid hydrate formation. These account for only a small amount of the fundamental understanding of gas hydrates and the use of such a novel technology.…”
Section: Introductionmentioning
confidence: 99%